Investigating the Social Relations of Community Gardens for Adult Education - McLarnon, Mitchell (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes, 2024)
This paper describes and analyzes the social relations that emerged from an ongoing adult education internship/community-based garden project in Montreal. I employ institutional ethnography to explore and uncover how adult education internships in community gardens and gardening programming can work to produce disproportionate outcomes for adult learners, community workers, and community members. I trace my own and others’ experiential knowledge of attempting to use gardens for social, environmental, and educational reasons into texts and policies that shape garden and adult education possibilities in community-based contexts. In the process of creating, funding, enacting, and evaluating adult education internships in community organizations, I elucidate specific institutional contrivances (e.g., funding, policy, work processes, discourse) that are presently structuring and defining who experiences access to gardens, gardening and its ostensible health and well-being benefits, and adult education.